Peran Guru Penggerak dalam Pendidikan Merdeka Belajar di Kubu Raya - Surahman Surahman; Redha Rahmani; Usman Radiana; Ardianus Imen Saputra (Jurnal Pendidikan Indonesia, 2022)
This article discusses the role of driving teachers in independent learning in Kubu Raya Regency. This article was developed through literature studies, the use of books and journals as well as other related documents. This article aims to provide an overview of the role of driving teachers in managing fun learning using existing technology so that students are encouraged to improve their academic achievements. The results of this study indicate that students are able to be independent according to aspects of the Pancasila student profile which require students to think critically, have noble character, be creative, work together, have global diversity, think critically and independently. Independent learning creates students not only knowing learning but having high analytical and reasoning skills in solving problems encountered in life. In addition, in the classroom, the driving teacher acts as a mentor and trainer for other teachers.